Impact of Semi-Fowler's Position in Chronic Heart Failure (CHF) Patients: Scoping Review - Ni Kadek Diah Purnamayanti; Santalia Bane Tondok; Wibowo Hanafi Ari Susasnto; Rohmani Rohmani (Postgraduate, University of Mataram, 2023)
Epidemic heart failure patients are a scourge of world health which has an increasing trend as old age increase. Heart failure is a state of heart function not adequately supplying blood for the body's metabolism, known as Congestive Heart Failuren the productive age population, CHF patients have high morbidity, frequent exacerbations, and mortality. Treatment in the hospital requires intensive care. One of the forms of treatment in question is positioning. Â This study aimed to determine the impact of the semi-fowler's position on CHF patients. The research design is a systematic review using Google Scholar, Pubmed, and Garuda searches. Inclusion criteria were the research of the last five years; all articles were available. Exclusion criteria are non-experimental research, such as literature and observational studiesâ€”critical review using the JBI checklist for quasi-experimental. The results of the study were seven experimental research articles in Indonesia, three studies only giving semi-fowler's position, two studies recommending semi-fowler's position is better than right/left, and two other studies recommending semi-fowler's + Fowler's and semi-fowler's' positions. This study concludes that the semi-fowler's position is the correct position in the treatment of CHF patients.